Dreaming the forced disappearance of people: The impossibility of presence and perennial of absence as effect of continuity of the civil-military dictatorship in Brazil's legacy (Psicologia USP, 2016)
This article discusses some social, political, and psychological effects of enforced disappearance as an effect of the strategies used during the Brazilian military dictatorship. Such strategies are buttressed and anchored at the certainty of impunity and indifference to the victims and survivors. One of the main consequences of this indifference today is the aggravation of the suffering of the family members that are still alive, which is preserved by the lethargy of the Brazilian state after the end of the dictatorship period, before the obligations to comply with the main international human rights resolutions relating to the combat of the forced disappearance of people. We recognize in the dream-work traces tracks and footprints of experiences that still insist and seek their status of language and social recognition 50 years after the civil-military coup in Brazil.